NANOSPONGES - A REVOLUTIONARY TARGETED DRUG DELIVERY NANOCARRIER: A REVIEW - ANKEM, BHAGYAVATHI; KUCHARLAPATI, SAI LAKSHMI TEJASWI; MAGAPU, SAHITYA DEEPTHI; B, BHAVANI (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Effective targeted drug delivery systems have long been a dream, but have been largely hampered by the complex chemistries involved in developing new systems. The creation of novel colloidal carriers known as nanosponges has the potential to resolve these issues. An innovative and developing technology called nanosponge provides regulated medication delivery for topical application. Highly porous nanosponges have a unique capacity to entrap active molecules and have the advantage of programmable release. Nanosponges are small three-dimensional porous structures about the size of nanometer that can contain many different drugs. These tiny sponges can move throughout the body until they meet a specific target site and attach to surfaces and begin to release the drug in a controlled and predictable manner. Because the drug can be delivered to a specific target site instead of circulating throughout the body, it is more effective for a given specific dose. They are easy to make and safe for biological use. Different types of cyclodextrins can be cross-linked using a carbonyl or a dicarboxylate chemical as a cross-linker to create nanosponges. This groundbreaking technology has been extensively investigated for the delivery of medications for oral, topical, and parental administrations. Vaccines, antibodies, proteins, and enzymes can all be effectively transported via Nanosponges. The current review emphasizes the methods, advantages, disadvantages, characterization, and applications of nanosponges.